Komodifikasi Perempuan sebagai Komoditas dalam Iklan Wardah #BeautyMovesYou di YouTube: Analisis Wacana Kritis Perspektif Feminisme Interseksional - Nur Rayhan Alhabsi; Rayhani Fajrianti; Rifma Ghulam Dzaljad (GLOBAL SCIENTS PUBLISHER, 2026)
Beauty product advertisements do not merely function as marketing media, but also as spaces that actively transform women into economic commodities. This study aims to analyze how women are commodified in Wardah's #BeautyMovesYou advertisement on YouTube, a 60-second campaign released in October 2021 featuring four main scenes of women moving to create change. The study employs a qualitative approach using Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA). Vincent Mosco's commodification concept is used to read how women's identities and values are transformed into exchange value, while Kimberlé Crenshaw's intersectional feminism is used to examine which identities are selectively commodified. The findings show that all four scenes commodify women's social values, from the spirit of collaboration, courage, education, to Muslim identity, as commercial brand assets. The inclusivity displayed is selective: only identities with high market value are represented, while lower-class, elderly, and ethnic minority women are absent. This study concludes that the empowerment narrative in Wardah's advertisement must be critically read as a femvertising practice.